The mechanism and therapeutic strategies for neovascular glaucoma secondary to diabetic retinopathy - Tang, Yizhen; Shi, Yan; Fan, Zhigang (Frontiers in Endocrinology, 2023)
Neovascular glaucoma (NVG) is a devastating secondary glaucoma characterized by the appearance of neovascular over the iris and the proliferation of fibrovascular tissue in the anterior chamber angle. Proliferative diabetic retinopathy (PDR) is one of the leading causes of NVG. Currently increasing diabetes population drive the prevalence rate of NVG into a fast-rising lane. The pathogenesis underlying NVG makes it refractory to routine management for other types of glaucoma in clinical practice. The combination of panretinal photocoagulation (PRP), anti-vascular endothelial growth factor (VEGF) injections, anti-glaucoma drugs, surgical intervention as well as blood glucose control are needed. Early diagnosis and aggressive treatment in time are crucial in halting the neovascularization process and preserving vision. This review provides an overview of NVG secondary to diabetic retinopathy (DR), including the epidemiology, pathogenesis and management, so as to provide a better understanding as well as potential therapeutic strategies for future treatment.